BIOMASSA DAN PENYERAPAN KARBON OLEH LAMUN Enhalus acroides DI PESISIR TELUK GUNUNG BOTAK PAPUA BARAT - Ferawati Runtuboi; Julius Nugroho; Yahya Rahakratat (Jurnal Sumberdaya Akuatik Indopasifik, 2018)
Seagrass is a high level and a flowering plant that is fully adapted to life in the coastal and has ability to store carbon by 10% of the carbon content in the oceans. The research doing at Gunung Botak Bay Coastal South Manokwari Regency with objective of research to estimate seagrass density and to estimate rate accumulation of carbon from Enhalus acroides. Some the stages of the research done is density sample as long to period 2015 (April and Mei) into (September and Ocktober). Other sampling to collecting seagrass to estimate carbon storage in part like daun, rhizome root and substrat. Result to showing average carbon accumulation of seagrass in above below ground is rhizome part and higher in Statiun1 (13.16±3.8),stasiun 3 (5.4±2.9) dan stasiun 5 (6.2±1.1) or the generally accumulation carbon in the three is 8.24 kg from Enhalus acroides. Future more, accumulation carbon in sediment as a 1664,2 in dept 0-20 cm and 20-60 cm. Seagrass carbon storage capabilities will assist in mitigation efforts to reduce the impact of climate change in Indonesia, especially in West Papua.